The active weak-line T Tauri star LkCa 4 observed with SPIRou and TESS. Issue 2 (25th January 2023) - Finociety, B; Donati, J-F; Grankin, K; Bouvier, J; Alencar, S; Ménard, F; Ray, T P; Kóspál, Á; consortium, the S L S
ABSTRACT: We report results of a spectropolarimetric and photometric monitoring of the weak-line T Tauri star LkCa 4 within the SPIRou Legacy Survey large programme, based on data collected with SPIRou at the Canada–France–Hawaii Telescope and the TESS space probe between October 2021 and January 2022. We applied Zeeman–Doppler Imaging to our spectropolarimetric and photometric data to recover a surface brightness distribution compatible with TESS photometry, as well as the large-scale magnetic topology of the star. As expected from the difference in wavelength between near-infrared and optical data, the recovered surface brightness distribution is less contrasted than the previously published one based on ESPaDOnS data, but still features mid-latitude dark and bright spots. The large-scale magnetic field is consistent in shape and strength with the one derived previously, with a poloidal component resembling a 2.2 kG dipole and a toroidal component reaching 1.4 kG and encircling the star at the equator. Our new data confirm that the surface differential rotation of LkCa 4 is about 10 times weaker than that of the Sun, and significantly different from zero. Using our brightness reconstruction and Gaussian Process Regression, we were able to filter the radial velocity activity jitter down to a precision of 0.45 and 0.38 km s^-1 (from an amplitude of 6.10 km s^-1 ), respectively, yielding again no evidence for a close-in massive planet orbiting the star.